Sexual Assault Case Attrition: The Voices of Survivors. (December 2022) - Murphy-Oikonen, Jodie; Chambers, Lori; Miller, Ainsley; McQueen, Karen
Sexual assault case attrition is pervasive within the criminal justice process. Despite initiating a police report following sexual victimization, many survivors make the decision to withdraw their police report and do not proceed with charges. Attrition of sexual assault cases at the point of entry to the criminal justice system is problematic for survivors as justice is not achieved and connections to support services are lacking. As such, the purpose of this research was to explore the first-hand account of sexual assault survivors who withdrew their report of sexual assault after disclosing the victimization to the police. Qualitative research was used to explore the experience of 14 sexual assault survivors who met the inclusion criteria for the study. Data collection included open-ended interviews that were audio-recorded, transcribed, and entered into NVIVO for analysis. Colaizzi's analytic method was used to analyze the data and resulted in the identification of three themes related to the decision not to pursue charges and a fourth theme describing the overall essence of the decision-making process. These themes included: (1) Overwhelming Police Process, (2) Police Communication about Charging/Process, (3) Loss of Faith in Justice System, and (4) No Hope. These findings provide insight from survivors supporting the saliency of the disclosure experience and the power of police communication. A trauma-informed police response during sexual assault disclosures is recommended based on the critical importance of supporting survivors, improving the investigative process, and holding perpetrators accountable. This approach may decrease attrition and improve justice for victims.